Microglia Express Mu Opioid Receptor: Insights From Transcriptomics and Fluorescent Reporter Mice - Maduna, Tando; Audouard, Emilie; Dembélé, Doulaye; Mouzaoui, Nejma; Reiss, David; Massotte, Dominique; Gaveriaux-Ruff, Claire (Frontiers in Psychiatry, 2019)
Background: Microglia activation contributes to chronic pain and to the adverse effects of opiate use such as analgesic tolerance and opioid-induced hyperalgesia. Both mu opioid receptor (MOR) encoded by Oprm1/OPRM1 gene and toll like receptor 4 (TLR4) have been reported to mediate these morphine effects and a current question is whether microglia express the Oprm1 transcript and MOR protein. The aim of this study was to characterize Oprm1-MOR expression in naive murine and human microglia, combining transcriptomics datasets previously published by other groups with our own imaging study using the Cx3cr1-eGFP-MOR-mCherry reporter mouse line. Methods: We analyzed microglial Oprm1/OPRM1 expression obtained from transcriptomics datasets, focusing on ex vivo studies from adult wild-type animals and adult post-mortem human cerebral cortex. Oprm1, as well as co-regulated gene sets were examined. The expression of MOR in microglia was also investigated using our novel fluorescent Cx3cr1-eGFP-MOR-mcherry reporter mouse line. We determined whether CX3cR1-eGFP positive microglial cells expressed MOR-mCherry protein by imaging various brain areas including the Frontal Cortex, Nucleus Accumbens, Ventral Tegmental Area, Central Amygdala and Periaqueductal Gray matter, as well as spinal cord. Results: Oprm1 expression was found in all 12 microglia datasets from mouse whole brain, in 7 out of 8 from cerebral cortex, 3 out of 4 from hippocampus, 1 out of 1 from striatum, and 4 out of 5 from mouse or rat spinal cord. OPRM1 was expressed in 16 out of 17 microglia transcriptomes from human cerebral cortex. In Cx3cr1-eGFP-MOR-mCherry mice, the percentage of MOR-positive microglial cells ranged between 35.4 and 51.6 % in the different brain areas, and between 36.8 and 42.4 % in the spinal cord. Conclusion: The comparative analysis of the microglia transcriptomes indicates that Oprm1/OPRM1 transcripts are expressed in microglia. The investigation of Cx3cr1-eGFP-MOR-mCherry mice also shows microglial expression of MOR proteinin the brain and spine. These results corroborate functional studies showing the actions of MOR agonists on microglia and suppression of these effects by MOR-selective antagonists or MOR knockdown.